Pengaruh Komitmen Organisasi, Motivasi, Lingkungan Kerja Dan Kepemimpinan Islami Terhadap Kinerja Karyawan (Studi Kasus Pada Karyawan Unisma) - Sutriman, Indah Ayu; Rizal, Mohammad; Utama, Satria Putra (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract The purpose of this study was to determine the effect of organizational commitment, Motivation, Work Environment and Islamic Leadership on Employee Performance. Data were taken using purposive sampling from 76 respondents through a questionnaire with a Likert Scale. Data analysis was performed using multiple linear regression and hypothesis testing (F test and t test). The results showed that simultaneously, the four variables had a positive and significant effect on employee performance (significance 0.000 < 0.05). However, partially organizational commitment, Work Environment and Islamic Leadership did not have a positive and significant effect on employee performance. Significance 0.072, 0.384 and 0.165 > 0.05). Keywords: Organizational Commitment, Motivation, Work Environment, Islamic Leadership and Employee Performance.